Removal of mercury (Hg) from contaminated water at traditional gold mining area in Central Kalimantan - Wahyu Wilopo; Denizar Rahman; Doni Prakasa Eka Putra; I Wayan Warmada (Geological Engineering Department Universitas Gadjah Mada, 2015)
There are many traditional gold mining and processing in Murung Raya Regency, Central Kalimantan. The processing of gold mostly uses mercury (Hg) and produces a lot of waste water. It just throws to the river without any treatment. Therefore the concentration of mercury (Hg) in the river water is over than the standard of drinking water and reach up to 0.346 mg dm-3. This situation is very dangerous because almost of the people in the downstream area depend on the river water for their daily purposes. To solve this problem, tuff from local material was used to remove mercury using batch experiment. The result showed that tuff has capability to remove mercury in the significant amount. The main mechanism of mercury removal by tuff is cation exchange processes due to high surface area of tuff. The result of this study can be used as an alternative for waste water treatment in mining area. Keywords: Traditional mining, mercury removal, tuff